FGF-2 is a driving force for chromosomal instability and a stromal factor associated with adverse clinico-pathological features in prostate cancer - Pecqueux, Carine; Arslan, Aysenur; Heller, Martina; Falkenstein, Michael; Kaczorowski, Adam; Tolstov, Yanis; Sültmann, Holger; Grüllich, Carsten; Herpel, Esther; Hohenfellner, Markus; Duensing, Stefan (Urologic oncology, 2018)
Background - There is mounting evidence to suggest that stromal cells play an integral role in the progression of prostate cancer (PCa). One of the most frequently altered growth factors in PCa is fibroblast growth factor-2 (FGF-2). It has previously been proposed that early stages of PCa are characterized by a primarily exogenous, that is, stromal cell-derived FGF-2 production, whereas advanced tumors rely more on an autocrine FGF-2 production. Prostate cancer progression is characterized by an increase of genomic instability including aneuploidy and structural chromosomal alterations. Herein, we address 2 problems that have not been comprehensively answered. First, we ask whether exogenous FGF-2 can directly drive genomic instability to promote PCa progression. Second, we investigate whether and to what extent stromal FGF-2 expression is maintained in advanced PCa and whether this influences tumor progression and patient prognosis. - Methods - In vitro experiments to investigate the role of FGF-2 in numerical and structural chromosomal instability were performed using immunofluorescence microscopy, fluorescence in situ hybridization and single cell electrophoresis. A human patient-derived xenograft mouse model recapitulating osteoblastic PCa bone metastasis was used for in vivo validation experiments. The prognostic role of stromal FGF-2 expression was analyzed using immunohistochemical staining of a tissue microarray with primary tumor specimens from 162 predominantly high-risk patients with PCa. - Results - Our results show that FGF-2 not only rapidly induces mitotic defects and numerical chromosomal imbalances but also an enhanced DNA breakage to promote chromosomal instability. Using the patient-derived xenograft model, we show that a deregulation of the FGF axis results in an increase of mitotic aberrations as well as DNA damage checkpoint activation in vivo. The FGFR inhibitor dovitinib was found to reduce numerical chromosomal instability as well as DNA breakage, thus underscoring the relevance of the FGF axis in promoting genomic instability. An overexpression of tumor cell-associated FGF-2 was detected in 52 of 162 patients (32.1%), whereas a stromal overexpression was found in 27 of 165 patients (16%). Remarkably, a strong stromal FGF-2 expression was associated with a significantly higher clinical stage and higher biochemical recurrence rate. Patients with strong stromal FGF-2 expression also had a significantly worse biochemical recurrence-free survival. - Conclusions - Our results underscore that exogenous FGF-2 can shape PCa cell genomes and that stromal FGF-2 expression is detectable in a sizeable proportion of advanced PCa where it is associated with adverse clinico-pathological features. Our results highlight the impact of the tumor stroma on malignant progression and provide a rationale for a further exploration of components of the tumor stroma as therapeutic targets in PCa.
Gesehen am 10.02.2020